The Holocaust and Hiroshima. Moral otherness and moral failure in war - Zimmermann, Rolf (Studia Philosophiae Christianae, 2019)
The 20th century was an age of extremes. In this article I concentrate on two disasters, the Holocaust and Hiroshima, in order to develop a philosophical reading of moral extremes under circumstances of war. My aim is to differentiate between these two events by exposing a normative framework. The significance of the Holocaust points to the phaenomenon of a rupture of species, which stands for a moral transgression never thought of. In analytical terms, this confronts us with the clashing of two normative orders: Firstly, the universal moral respect of every human being; secondly, the radical particularism of Nazism. To denounce the moral otherness of the latter is to highlight the war aims of Nazism: imperial aggression to dominate Europe, and annihilation of the Jews as a world-historical mission. In view of both aims, war against Nazism was just. The moral disaster of Hiroshima, however, stands in marked contrast to this characterization. The political leaders of the US did not intend to annihilate the Japanese people; they thought they would end war by making use of a nuclear weapon. It is, therefore, a misleading metaphor to speak of a “nuclear holocaust”, or to allude to a genocidal action in this case. This does not mean at all that dropping the bomb was justified. Quite contrary to the US official stance, it is important to consider this event in moral terms by relying on precise historical circumstances and well-founded critical analysis. There is strong evidence that it was a moral failure to opt for the bomb. This comes close to the diagnosis of a war crime within a just war framework. Nevertheless, this diagnosis must be kept distinct from the type of crime involved in the Holocaust.